Gamma knife radiosurgery for primary orbital varices: a preliminary report. Issue 9 (22nd October 2010) - Xu, Desheng; Liu, Dong; Zhang, Zhiyuan; Zhang, Yipei; Song, Guoxiang
Abstract : Aim: The aim of this retrospective study is to evaluate the authors' experience using gamma knife radiosurgery in the management of primary orbital varices. Methods: Fourteen patients, six males and eight females, with ages ranging from 7 to 56 years of age, were treated with gamma knife radiosurgery from April 2001 to June 2005 for primary orbital varices. The median prescription peripheral dose was 16 Gy, ranging from 15 to 20 Gy, and the median maximum dose was 32 Gy, ranging from 30 to 40 Gy. The median volume of the lesion at radiosurgery was 4.5 ml (range 1.9 ml to 9.0 ml). The mean dose to optic nerve was below 10 Gy. A mean of 10 isocentres (range 8 to 13) were used for treating these lesions. Results: At a median follow-up period of 36 months (range 18 to 66 months), recurrent exophthalmos and diplopia resolved in 10 patients. Two of the remaining four patients showed evidence of decrease in distensibility, while the other two remain unchanged. The median time of their presenting symptoms resolving was 7 months (range 3 to 18 months). One patient lost her sight 18 months after gamma knife radiosurgery. No patient had intraorbital haemorrhage after treatment. Conclusion: Gamma knife radiosurgery provides effective long-term relief of symptoms in selected patients with primary orbital varices.